Psychological First Aid (PFA) Pada Korban Erupsi Gunung Sinabung Di Kabupaten Karo - Syapitri, Henny; Aryani, Novita; Marbun, Agnes Silvina (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2023)
Mount Sinabung is one of the highest mountains (2,460 meters) active in North Sumatra, in addition to Mount Sibayak, which is located in the highlands of Tanah Karo. Natural disasters usually have an impact on infrastructure damage and job opportunities, damage and even loss, Therefore, An intervention that is used to overcome the initial emotional reaction above is Psychological First Aid (PFA). The purpose of this community service activity is to carry out psychological first aid (PFA) on victims of the eruption of Mount Sinabung, Karo Regency. The method used is to overcome existing problems. is to provide PFA training to victims of the eruption of Mount Sinabung. The characteristics of participants who have a psychological background. The result of this activity is that the enthusiasm of the participants in this activity is very high, as evidenced by the seriousness of the participants in doing PFA skill roleplay. The average result of the pre-test for Psychological First Aid (PFA) is 3.14, while the post-test results show an average score of 9.86. Based on these data shows an increase in the average value of 6.72. The difference in values ​​is the result of the understanding gained by the participants after participating in Psychological First Aid (PFA) training.